Revisiting the work-suicide link: renewed evidence and models of analysis in workplace contexts - Llosa, José Antonio; Agulló-Tomás, Esteban; Menéndez-Espina, Sara; Oliveros, Beatriz (Frontiers in Psychology, 2023)
Suicide is a priority public health problem for the World Health Organization. It is a multifactorial phenomenon, for which there is no effective strategy for prevention and reduction. The scientific knowledge generated has not paid much attention to the differentiating role of work and employment on the phenomenon of suicide. This article first presents Abrutyn’s recent conceptual model of suicide, which has a psychosocial, holistic and integrated approach. Based on this model, it examines the most recent and solid evidence and trends linking working conditions and phenomenon of suicide, identifying the most relevant findings in work stress theories. It concludes by pointing out avenues of development for a more holistic and ecological understanding of suicide.